Models for droplet heating and evaporation: an application to biodiesel, diesel and gasoline fuels. (2017) - Qubeissi, Mansour Al; Sazhin, Sergei S.
This paper presents our recent progress in the modelling of automotive fuel droplet heating and evaporation processes in conditions close to those in direct-injection internal-combustion engines. Three types of automotive-fuels are considered: biodiesel, diesel and gasoline fuels. Modelling of biodiesel fuel droplets is based on the application of the discrete component (DC) model. A distinctive feature of this model is that it is based on the analytical solutions to the transient heat conduction and species diffusion equations in the liquid phase, taking into account the effects of recirculation. The application of the DC model to fossil fuels (containing potentially hundreds of components), however, is computationally expensive. The modelling of these fuels is based on the recently introduced multi-dimensional quasi-discrete (MDQD) model. This model replaces a large number of components in diesel and gasoline fuels with a much smaller number of quasi-components/components without losing the main features of the original DC model. The MDQD model is shown to accurately predict droplet temperatures and evaporation times and to be much more computationally efficient than the DC model. The main features of these models and their applications to three types of automotive fuel droplets are summarised and discussed.